ANALISIS KEPUASAN KONSUMEN MADU LOKAL DI KOTA PONTIANAK - Natalia Lelo Mali; Eva Dolorosa; Novira Kusrini (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Honey is a natural substance that bees produce from flower-neutral raw materials. Honey is one of the commodities of non-timber forest products that provide many benefits. The purpose of this research was to analyze the satisfaction of  the honey consumers to Syaiful in Pontianak city. In this study there were 100 key respondents to answer questionnaires. Through five dimensions namely product quality dimensions, service quality dimensions, price dimensions, emotional dimensions, and ease dimensions will be known attributes - what attributes need to be maintained, performance, improved or reduced and determine the top priority, maintain achievements, low priority and excessive priority into cartesian diagrams. Respondents with accidental sampling who happened to meet with researchers to be analyzed using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). IPA results showed that the dimensions of consumer satisfaction that became the main priority in improving the performance of its implementation are honey color, honey aroma, neat-looking employees, affordable prices, prices according to product quality, proud to consume local honey. CSI results showed that the contingency satisfaction level in Syaiful honey shop fell into the category of satisfied with avalue of 71.20%.